Eco Digital Clock / Nadia Athira Yunus ...[et al.] - Yunus, Nadia Athira; Nik Baharudin, Nik Nurfadzillah; Sabri, Nur 'Atikah; Azman, Nurul Haziqah; Abu Bakar Sonny, Nurul Najwa Zulaikha; Nahar, Zulemalina (2019)
Our team has come out with an innovation which is called 'Eco Digital Clock'. This innovation is an improvement of the existing digital clock that is offered in the market nowadays. Instead of using lithium battery as the power source of the digital clock, the team proposed to use plant to generate electricity in order for the digital clock to function. This is the team's approach to reduce environmental pollution by using green technology that is friendly to the earth's ecosystem. There are numerous potential toxic risks related with emission of battery chemicals into aquatic ecosystems. Inapplicable or irresponsible management of waste batteries can proceed to spilling cf corrosive liquids and dissolved metals that are lethal to plants and animals. Improper disposal of V batteries in landfill sites can result in the release of toxic substances into groundwater and the environment. By using plant, this is the latest viable source of renewable energy and it is earth abundant natural sources. Unlike biogas, which is produced by the anaerobic digestion or fermentation of biomass, the Plant-Microbial Fuel Cell (PMFC) generates electricity while the plants continue to grow. Importantly, researchers has study and conclude that the system does not affect the plant's growth or harm the environment. The idea behind this innovation is because of attentiveness of our team towards the global pollution that is currently happening. Pollution is the primary environmental contributing factor of disease and premature death in the world, accounting for three times more deaths in 2015 than AIDS, tuberculosis and malaria combined. The report by the Lancet Commission on Pollution and Health blames pollution for an estimated nine million premature deaths. This conclude that pollution endangers the stability of the earth's support system and threatens the continuing survival of human society. Therefore, we would like to promote the team's idea in order to save the world to a better place to live. Our team has targeted few categories of people which will specifically interest with this innovation. The groups that we aim are office workers, students and environmentalist. Nevertheless, the team would not limit to only the targeted group but it is open to people that are interested to support green technology products. By proposing and developing this product, we hope to give awareness to our customers and bring benefit to the world's condition